2018
DOI: 10.1155/2018/4079087
|View full text |Cite
|
Sign up to set email alerts
|

Women with Type 1 Diabetes Mellitus: Effect of Disease and Psychosocial-Related Correlates on Health-Related Quality of Life

Abstract: Background This study is aimed at investigating the various disease-specific and health-related psychosocial concepts of HRQOL among insulin-dependent diabetes mellitus (IDDM) and understanding the gender differences in HRQOL among IDDM patients. Methods A cross-sectional observational study was conducted to assess the effect of health-related and psychosocial correlates on HRQOL of IDDM patients in Penang, Malaysia. The participants were recruited from five governmental diabetic clinics. Patients with insulin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
5

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 24 publications
0
7
0
5
Order By: Relevance
“…The value score of the EQ-5D-3L visual analog scale index also indicated significantly low indices among OAM users. 10 , 13 The negative influence of T2DM on HRQoL and health state is widely reported across the world, 15 , 24 , 25 but current apprehension focuses on the reversibility of such deteriorating effects with rational treatment modalities. This study also reported that insulin users had a better and improved HRQoL compared with OAM use only.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The value score of the EQ-5D-3L visual analog scale index also indicated significantly low indices among OAM users. 10 , 13 The negative influence of T2DM on HRQoL and health state is widely reported across the world, 15 , 24 , 25 but current apprehension focuses on the reversibility of such deteriorating effects with rational treatment modalities. This study also reported that insulin users had a better and improved HRQoL compared with OAM use only.…”
Section: Discussionmentioning
confidence: 99%
“…Medication adherence, diabetes-related knowledge, and patient satisfaction are the potential parameters for improving HRQoL. 15 None of the studies have discussed these factors among Malaysian populations. Malaysia is a multiethnic society with different lifestyle patterns and religious practices, 2 , 3 , 8 , 9 mainly consisting of Malay, Chinese, and Indian ethnicity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our findings have also shown that fenugreek improves the quality of life of patients with T2DM, probably because of the management of the disease by fenugreek treatment. Studies have demonstrated that diabetes management can positively affect the quality of life of diabetic patients [ 34 , 35 ]. The effects of anti-diabetic and cholesterol reduction by fenugreek seeds largely has been attributed to saponins and its high fiber content which delays gastric emptying and unknown components that constrain carbohydrate digestive enzymes [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings have also shown that fenugreek improves the quality of life of patients with T2DM, probably because of the management of the disease by fenugreek treatment. Studies have demonstrated that diabetes management can positively affect the quality of life of diabetic patients [34,35]. The effects of anti-diabetic and cholesterol reduction by fenugreek seeds largely has been attributed to saponins and its high fiber content which delays gastric emptying and unknown components that constrain carbohydrate digestive enzymes [36].…”
Section: Discussionmentioning
confidence: 99%